Bahasa Inggris: Bahasa Inggris - Permatasari, Novelia Kiki; Sutihat, Eva; Yunita, Irma; Yuliana, Ade (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2025)
This study investigates the impact of halal branding, brand image, and brand trust on purchasing decisions among Micro and Small Enterprises (MSEs). It contributes to academic discourse by examining how gender equality interacts with brand-related variables within the framework of the Sustainable Development Goals (SDGs)—a perspective rarely addressed in existing literature. Using data from 400 MSE actors selected through cluster sampling and analyzed via PLS-SEM, the study finds that halal branding, brand image, and brand trust each exert a positive and significant influence on consumer decisions. Interestingly, gender equality does not reinforce these relationships but instead appears to weaken them, suggesting that consumer responses may be shaped by deeper cultural and social currents. The findings encourage business actors to view halal branding and trust-building not merely as technical strategies but as part of a broader engagement with community values—requiring locally grounded approaches to gender inclusion and improved relationships.